Unusual pseudocyst in a wandering spleen. Issue 9 (5th September 2019) - Manoharan, Dinesh; Kumar, Atin; Krishna, Asuri; Bansal, Virinder Kumar
Abstract : Pseudocysts of the spleen are rare, generally asymptomatic lesions developing secondary to trauma, infection or infarction. When symptomatic, they typically present as non-specific pain in the left hypochondrium, with or without a palpable lump on clinical examination. However, these conventions fail when they occur in a wandering spleen, making imaging critically important. This report describes an unusual case of a 50-year-old who presented with a large cystic mass in a pelvic spleen; imaging facilitated a successful splenectomy and subsequent histopathology revealed a pseudocyst in a wandering spleen.